The Effect of Hanging Ball Media Training on Improving Smash Skills in Volleyball Games in the Men's Team at Club PVG Garut - Ani Kurniawati; Z. Arifin; Restu Kusnandi (CV Media Inti Teknologi, 2024)
This study aims to determine the effect of hanging ball media training on improving smash skills in volleyball games on the men's team at the Garut PVG club. Hanging ball media is a solution or strategy in practicing smash accuracy. Hanging ball smash training aims to provide habituation for athletes in measuring and knowing the height of the jump so that when playing volleyball athletes can hit the ball on target. Hanging ball training is a jumping exercise to reach the target ball by increasing the height of the hanging ball. The method used is experimental research method. The results showed that there was an effect of hanging ball media training in improving the smash skills of members at Club PVG Garut. This is evidenced by the calculated significance value in the pretest and posttest group t test of 0.017 smaller than 0.05 (Sig <0.05). The conclusion in this study is that there is an effect of training with hanging ball media on smash skills in volleyball games on the men's team of the Garut PVG club. In training with hanging balls that are carried out continuously can improve the ability of smash skills.